NQO-Induced DNA-Less Cell Formation Is Associated with Chromatin Protein Degradation and Dependent on A0A1-ATPase in Sulfolobus - Han, Wenyuan; Xu, Yanqun; Feng, Xu; Liang, Yun X.; Huang, Li; Shen, Yulong; She, Qunxin (Frontiers in Microbiology, 2017)
Abstract To investigate DNA damage response in the model crenarchaeon Sulfolobus islandicus, four different DNA damage agents were tested for their effects on cell death of the archaeon, including UV irradiation, methyl methanesulfonate (MMS), cisplatin and 4-nitroquinoline 1-oxide (NQO). Cell death featured with DNA-less cell formation was revealed in DNA damage treatment with each agent. Cellular responses upon NQO treatment were characterized in more details, and following sequential events were revealed, including: a modest accumulation of G1/S phase cells, membrane depolarization, proteolytic degradation of chromatin proteins and chromosomal DNA degradation. Further insights into the process were gained from studying drugs that affect the archaeal ATP synthase, including a proton gradient uncoupler and an ATP synthase inhibitor. Whereas the proton uncoupler-mediated excess proton influx yielded cell death as observed for the NQO treatment, inhibition of ATP synthase attenuated NQO-induced membrane depolarization and DNA-less cell formation. In conclusion, the NQO-induced cell death in S. islandicus is characterized by proteolytic degradation of chromatin protein, and chromosomal DNA degradation, which probably represents a common feature for the cell death induced by different DNA damage agents.